2022
DOI: 10.3390/nano12122074
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Exposure of Graphene Nanoplates on the Viability and Motility of A549 Cells

Abstract: Graphene and its derivatives are popular nanomaterials used worldwide in many technical fields and biomedical applications. Due to such massive use, their anticipated accumulation in the environment is inevitable, with a largely unknown chronic influence on living organisms. Although repeatedly tested in chronic in vivo studies, long-term cell culture experiments that explain the biological response to these nanomaterials are still scarce. In this study, we sought to evaluate the biological responses of establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…By the same token 46 , Jin et al 47 demonstrated that graphene oxide can enter into A549 cells, being located in the cytoplasm and nucleus, without affecting the viability of the cells. Furthermore, Šestáková et al 48 determined by TEM the presence of graphene platelets in A549 cells after an 8-week exposure, suggesting that the cells can enclose graphene platelets, which were free in the cytoplasm into the membrane-bound vesicles. Regarding HT-29 cells, recently it was described the internalisation of graphene oxide (GO) by differentiated cells 49 .…”
Section: Discussionmentioning
confidence: 99%
“…By the same token 46 , Jin et al 47 demonstrated that graphene oxide can enter into A549 cells, being located in the cytoplasm and nucleus, without affecting the viability of the cells. Furthermore, Šestáková et al 48 determined by TEM the presence of graphene platelets in A549 cells after an 8-week exposure, suggesting that the cells can enclose graphene platelets, which were free in the cytoplasm into the membrane-bound vesicles. Regarding HT-29 cells, recently it was described the internalisation of graphene oxide (GO) by differentiated cells 49 .…”
Section: Discussionmentioning
confidence: 99%